Electrospun Polycaprolactone/Aloe Vera_Chitosan Nanofibrous Asymmetric Membranes Aimed for Wound Healing Applications - Borges, Paula Isabel (2018)
Today, none of the wound dressings available on the market is fully capable of reproducing all the features of native skin. Herein, an asymmetric electrospun membrane was produced to mimic both layers of skin. It comprises a top dense layer (manufactured with polycaprolactone) that was designed to provide mechanical support to the wound and a bottom porous layer (composed of chitosan and Aloe Vera) aimed to improve the bactericidal activity of the membrane and ultimately the healing process. The results obtained revealed that the produced asymmetric membranes displayed a porosity, wettability, as well as mechanical properties similar to those presented by the native skin. Fibroblast cells were able to adhere, spread, and proliferate on the surface of the membranes and the intrinsic structure of the two layers of the membrane is capable of avoiding the invasion of microorganisms while conferring bioactive properties. Such data reveals the potential of these asymmetric membranes, in the near future, to be applied as wound dressings.